Rationalization and the deprofessionalization of physicians - Ritzer, George [Verfasser]; Walczak, David [Verfasser] (My University, 1988)
"The Weberian theory of rationalization, especially the concepts of formal and substantive rationality and the conflict between them, are used to analyze contemporary changes affecting the medical profession. Three major types of changes are discussed - changes in government policies, the changing nature of medical delivery systems, and changes within medical delivery systems. It is argued that these changes are impelling the medical profession away from substantive rationality and in the direction of formal rationality. Increasing formal rationality is likely to lead to greater external control over physicians and to a decline in the ability of the medical profession to distinguish itself from bureaucrats and capitalists. These changes, in turn, are likely to lead to some degree of deprofessionalization of physicians. Alternative future scenarios are also mentioned." (author's abstract) ((en)) Die Wandlung des Arztberufes in den Vereinigten Staaten wird auf der Grundlage von Weber's Theorie der Rationalisierung, speziell des Konzepts der formalen und materiellen Rationalität, analysiert. Drei Haupttypen des Wandels werden diskutiert: Änderungen der Regierungspolitik, der sich wandelnde Charakter des medizinischen Versorgungssystems und der Wandel innerhalb des Versorgungssystems. In diesem Zusammenhang wird nachgewiesen, dass der Arztberuf von substantieller Rationalität zu materieller Rationalität getrieben wird, was zu einer Deprofessionalisierung von Ärzten führen kann. (IAB)
Rationalisierung und Deprofessionalisierung von Ärzten
Keywords: S 6.4.5.1 Ärzte, Apotheker; G 2.3.4 Qualifikationswandel; Arzt; Entberuflichung; Rationalisierung; Berufsproblem